Pendampingan Potensi Ekonomi Desa Kalirejo Undaan Kudus Berbasis Moderasi Beragama - Kharis Fadlullah Hana; M. Ghozinul Asror; Mushoffa Najih; Hamzah Said Romdhoni; Masfufatul Lailiyah; Sufiana Noor (Jurnal Pengabdian Masyarakat (abdira), 2022)
The problem of radicalism and the politicization of religion has become increasingly prevalent in recent years. Disputes between communities as a result of blaming each other between religions are an important problem to be resolved immediately. As a result, togetherness to increase regional economic potential has also stalled with a lack of tolerance between religious communities. Therefore, this service activity aims to provide assistance to the community in order to increase the economic potential of the village based on religious moderation. The method used is Participatory Action Research (PAR) by involving the community to actively participate in developing the economic potential of the Kalirejo village. Kalirejo Village was chosen as the object of service because it has economic potential in the form of a large village market, quite a lot of MSMEs and the community has 3 religions that coexist, namely Islam, Buddhism and Christianity. The results of this service are enthusiastically accepted by the community and can increase religious literacy. In addition, the economic potential of the village can be explored and documented into the book Pesona Desa Kalirejo.